2015
DOI: 10.1038/cdd.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

The LIM-only transcription factor LMO2 determines tumorigenic and angiogenic traits in glioma stem cells

Abstract: Glioblastomas (GBMs) maintain their cellular heterogeneity with glioma stem cells (GSCs) producing a variety of tumor cell types. Here we interrogated the oncogenic roles of Lim domain only 2 (LMO2) in GBM and GSCs in mice and human. High expression of LMO2 was found in human patient-derived GSCs compared with the differentiated progeny cells. LMO2 is required for GSC proliferation both in vitro and in vivo, as shRNA-mediated LMO2 silencing attenuated tumor growth derived from human GSCs. Further, LMO2 is suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
0
41
1
Order By: Relevance
“…The oncogenic role of LMO2 was also supported by studies in glioblastoma28 and prostate carcinoma11. However, in recent years several reports have suggested that LMO2 is a biomarker for good prognosis in DLBCL293031, acute B-lymphocytic leukemia32, and pancreatic carcinoma12, suggesting that LMO2 could also function as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 92%
“…The oncogenic role of LMO2 was also supported by studies in glioblastoma28 and prostate carcinoma11. However, in recent years several reports have suggested that LMO2 is a biomarker for good prognosis in DLBCL293031, acute B-lymphocytic leukemia32, and pancreatic carcinoma12, suggesting that LMO2 could also function as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 92%
“…A function in tumor angiogenesis had not been previously described, however, and while LMO2 has been implicated in physiologic [60] and pathologic [44, 61, 62] angiogenesis, these studies provide the first evidence for LMO4 involvement in this process. This may have relevance to other epithelial malignancies in which this LIM-only protein is overexpressed, in particular carcinoma of the breast.…”
Section: Discussionmentioning
confidence: 54%
“…While these studies add to a considerable literature demonstrating that LMO and associated LIM domain binding proteins can be pro-oncogenic [5, 13, 16, 44], less is known about the involvement or function of SSBPs in cancer. Although increased SSBP2 expression was associated with shorter survival in glioblastoma [45], SSBP2 was also shown to inhibit the growth of prostate cancer cells [46] and to act as a tumor suppressor in myeloid leukemias [21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LMO2 has been shown to promote angiogenic traits in glioma stem cells [23]. It has been shown in zebrafish, that knockdown of Lmo2 , via morpholino, resulted in defective intersegmental vessels [24].…”
Section: Introductionmentioning
confidence: 99%